1999
DOI: 10.1292/jvms.61.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lipopolysaccharide on Production of Interleukin-1 and Interleukin-6 by Bovine Mammary Epithelial Cells in vitro

Abstract: ABSTRACT. This investigation was performed to determine the effect of lipopolysaccharide (LPS) on production of interleukin (IL)-1 and IL-6 by bovine mammary epithelial cells in vitro. After confluence, the cells were stimulated with LPS (0.1, 1.0 or 10 µg/ml) for 4, 8, 24, and 48 hr. LPS increased production of both IL-1 and IL-6 production from mammary cells in a dose dependent manner. The expression of mRNA for IL-1 receptor antagonist (IL-1ra) was demonstrated by reverse transcription-polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 14 publications
0
21
1
Order By: Relevance
“…In vitro, LPS stimulation increased the production of both IL-1 and IL-6 from cryopreserved MEC in a dose-dependent manner [118]. IL-1 and IL-6 are both important mediators of inflammation including stimulation of the acute phase response and in vivo, IL-1β was detected in milk from cows suffering from mastitis [6,7,153].…”
Section: Contribution Of Mammary Epithelial Cellsmentioning
confidence: 90%
“…In vitro, LPS stimulation increased the production of both IL-1 and IL-6 from cryopreserved MEC in a dose-dependent manner [118]. IL-1 and IL-6 are both important mediators of inflammation including stimulation of the acute phase response and in vivo, IL-1β was detected in milk from cows suffering from mastitis [6,7,153].…”
Section: Contribution Of Mammary Epithelial Cellsmentioning
confidence: 90%
“…This makes them a suitable model to address the effect of soluble mediators and ET on mammary cell function (Talhouk et al 2000b(Talhouk et al 2001. In contrast to other studies on either primary bovine mammary cells or MAC-T bovine epithelial cell line (Boudjellab et al 1998, Okada et al 1999) that where limited to monitoring the effect of ET on cytokine production, in this study, we monitored, in addition to cytokine and NGF production, the effect of ET on NF-kB activation and on the differentiation phenotype as indicated by b-casein and gelatinase expression. The data presented in this study showed that daily exposure of confluent CID-9 cells on EHS-drip to ET concentrations up to 10 mg/ml did not alter the apparent morphology (data not shown) and the viability of CID-9 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines play important roles in the outcome of infectious diseases and inflammation [9]. The inflammatory cytokines IL-1, IL-6 and TNF-α are the principal mediators of natural immunity against gram-negative bacteria and are key mediators of inflammatory response and septic shock [14]. Susceptibility or tolerance to various infectious diseases is associated with the expression of particular cytokine profiles.…”
mentioning
confidence: 99%